2008
DOI: 10.1002/ijc.23764
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy

Abstract: Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 60 publications
(92 reference statements)
8
99
0
2
Order By: Relevance
“…33 In colorectal cancer, GBP1 overexpression in tumor stroma inhibits tumor growth and correlates with improved survival. 34,35 The functions of other GBPs are less clear although animal and in-vitro models suggest a protective role in controlling infection and autoimmunity as GBPs are essential for formation of the inflammasome complex. 36 The inflammasome complex promotes inflammatory cell death through activation of cysteine protease caspase-1 and is purported to have tumor suppressive effects in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…33 In colorectal cancer, GBP1 overexpression in tumor stroma inhibits tumor growth and correlates with improved survival. 34,35 The functions of other GBPs are less clear although animal and in-vitro models suggest a protective role in controlling infection and autoimmunity as GBPs are essential for formation of the inflammasome complex. 36 The inflammasome complex promotes inflammatory cell death through activation of cysteine protease caspase-1 and is purported to have tumor suppressive effects in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent evidence is accumulating showing that hGBP-1 is involved in antitumoral response processes. In a study involving 388 patients with colorectal carcinomas (20), robust hGBP-1 expression was detected in 30% of the tumors in endothelial cells and monocytes of the desmoplastic stroma. Most interestingly, this finding was associated with a reduced tumor angiogenesis and a highly significantly improved prognosis for the patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…The antiangiogenic activity of hGBP-1 has been recently demonstrated for colorectal carcinomas. In a study investigating more than 380 tumor samples, it was shown that tumors expressing hGBP-1 exhibited reduced angiogenic activity, and this was associated with a significantly improved prognosis for the respective patients (20). In addition, an effect on proliferation of fibroblasts has been demonstrated for murine GBP-2 (21).…”
Section: Introductionmentioning
confidence: 99%
“…The CXC chemokines (CXCL9, CXCL10 and CXCL11) inhibit endothelial cell proliferation [67] and suppress tumor angiogenesis in diverse tumors [68][69][70]. Therefore, the balance of angiogenic ELR + vs. angiostatic non-ELR chemokines produced in the tumor microenvironment may determine the development of angiogenesis within a tumor tissue and the consequent clinical outcome.…”
Section: Angiogenesis and Matrix Remodelingmentioning
confidence: 99%